Sistem Manajemen Baterai Pada Peralatan Catu Daya Di Equipment Room Stasiun Manggarai Dengan Aplikasi Blynk Berbasis Esp8266 - Tito Ahmad Fauzan; Rahman Arifuddin; Resi Dwi Jayanti Kartika Sari (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This research aims to develop an efficient battery monitoring system using the ESP8266 module and INA219 sensor. Monitoring the battery condition effectively is crucial in various applications, especially in portable systems or isolated systems where real-time supervision is required. The method used in this research is the utilization of the ESP8266 module as the main microcontroller connected to the INA219 sensor to monitor the battery voltage, current, and power in real-time. The data obtained by the INA219 sensor is transmitted through the WiFi network managed by ESP8266 to a server or monitoring platform accessible to users via Blynk a web-based application or mobile application. The test results show that the system is capable of providing accurate information about the battery condition, including the charge level, usage current, and potential issues such as overcharge or undercharge. The implementation of this system is expected to be applicable in various applications, including renewable energy systems, portable devices, and electric vehicles, to improve battery performance and safety. The INA219 module as a voltage and current sensor found a voltage reading error percentage with a range of 0%-0.66% and an average of 0.18%. For readings at current with an error range of 0.91%-7.57%. For internal resistance readings which are calculated based on dividing the clamp voltage value by the circuit current, an error range of 0.04% -30.36% is found.